Dynamics of Social Interaction Between Residents in Urban Environments - Samsidar, Samsidar (PT. Anagata Sembagi Education, 2025)
In the era of increasingly rapid urbanization, the dynamics of social interaction between residents in urban environments have undergone various significant changes. This study aims to analyze the forms, influencing factors, and challenges and opportunities in social interaction between city residents. Using a qualitative approach with in-depth interview techniques and participant observation, this study reveals that social interaction in urban environments is characterized by diverse social backgrounds, a fast pace of life, and limitations of space and time. The findings show two main tendencies: increasing individualism and the formation of micro-communities based on common interests. Obstacles such as social inequality, distrust between residents, and lack of public space also limit the intensity of social interaction. However, social media and online communities have become new spaces that expand the forms of interaction between residents. This study recommends the need to strengthen inclusive and locally-based social interaction spaces in urban environments to strengthen the social cohesion of urban communities.